Isolation of Aeromonas hydrophila from Commercial Chickens in Jos Metropolis, Nigeria - Dashe , Y.G.; Raji, M.A.; Abdu, P.A.; Oladele, B.S.; Olarinmoye, D. (International Journal of Poultry Science, 2013)
Aeromonas species are increasingly incriminated in clinical cases in livestock and humans in Nigeria and the world at large. This investigative study was carried out between November, 2010 and October, 2011 in Jos, Nigeria to determine the isolation rate of Aeromonas species in clinically sick and apparently healthy commercial chickens. A total of 2000 postmortem samples consisting of bone marrow, heart, liver, lung and spleen (400 each) were aseptically collected from 400 clinically sick chickens suspected to be suffering from various clinical conditions and cultured for Aeromonas organisms. Four hundred oro-pharyngeal swabs were also collected from 400 apparently healthy chickens for bacteriological analysis. Swab from each sample was cultured on 7% defibrinated sheep blood and MacConkey. From the bacteriological cultures of the bone marrow, heart and liver of the sick chickens, a total 11 (0.5%) Aeromonas hydrophila isolates were identified by biochemical characterization and Macrobact™ test. Aeromonas organism was not isolated at all from the apparently healthy chickens. The co-occurrence of Aeromonas hydrophila with other pathogens in the sick chickens could have contributed to the observed exacerbation of clinical signs and mortalities in some of the investigated flocks during the study period.